Pneumococcal Vaccination Coverage and Uptake Among Adults in Switzerland: A Nationwide Cross-Sectional Study of Vaccination Records - Zens, Kyra D.; Baroutsou, Vasiliki; Fehr, Jan S.; Lang, Phung (Frontiers in Public Health, 2022)
Streptococcus pneumoniae, or pneumococcus, is a common, opportunistic pathogen which can cause severe disease, particularly in adults 65+. In Switzerland, vaccination is recommended for children under 5 and for adults with health predispositions; vaccination of healthy adults 65+ is not recommended. In 2020 we conducted a nationwide, cross-sectional survey of vaccination records to evaluate pneumococcal vaccination coverage and factors affecting uptake among adults 18-85. We found that nationwide coverage was 4.5% without significant regional differences. Coverage was comparable between men and women and between those aged 18-39 (3.0%) and 40-64 (3.2%). Coverage was significantly higher among those 65-85 (9.6%). While 2.7% of individuals reporting no health predisposition were vaccinated, 14.8% with asthma or chronic pulmonary disease, 27.1% with immunosuppression, 12.9% with diabetes, 11.6% with heart, liver, or kidney disease, and 25.9% >1 health risk were vaccinated. Adjusted odds of vaccination for all health predispositions except heart, liver, or kidney disease were significantly increased. Among unvaccinated individuals “not enough information about the topic” and “not suggested by a doctor/healthcare provider” were the major reasons for abstaining from vaccination. Respondents reporting a health predisposition were significantly less likely to report “not at increased risk due to chronic health conditions or age” as a reason for not being vaccinated (3.7% versus 29.1%) and were more likely to report willingness to be vaccinated in the future compared to those not-at-risk (54.2% versus 39.9%). Our results indicate that pneumococcal vaccination coverage in Switzerland is low among both individuals 65-85 and those with predisposing health risks. It appears that at-risk individuals are aware of their increased risk, but feel they do not have enough information on the topic to seek vaccination, or have not been recommended a vaccination from their physician.